Effect of Principal Leadership, Teaching Quality, and Student Motivation on Academic Performance in Senior High Schools - Pattasang Pattasang; Martinis Yamin; Maisah Maisah (PT. Riset Press International, 2025)
This study aims to analyze the influence of school principal leadership, teaching quality, and student motivation on academic achievement at private senior high schools in the Riau Islands Province. The research method used is quantitative with a survey approach. The sample consisted of eight randomly selected private senior high schools. Data were collected using questionnaires and analyzed using Structural Equation Modeling to examine both direct and indirect effects among variables. The results showed that school principal leadership had a positive and significant effect of 12.2% on students' academic achievement. Teaching quality had a positive influence of 20.1%, and student motivation contributed 9.6% to academic achievement. Simultaneously, principal leadership and teaching quality contributed 26.3% to students' academic achievement. Furthermore, principal leadership and teaching quality significantly influenced student motivation, contributing 22.4% and 28.1% respectively, and jointly 30.6%. Student motivation acted as a mediating variable that strengthened the influence of principal leadership (15.3%) and teaching quality (17.4%) on academic achievement. Based on these findings, it is recommended that principals improve their leadership, teachers enhance their teaching quality, and students increase their learning motivation to support the improvement of academic achievement in private senior high schools in the Riau Islands Province.